Analisis Kebijakan Pemerintah Dalam Penanggulangan Bencana Banjir di Wilayah Pakal Surabaya Barat - Jihan Rosyidah, Silvia; Putri, Luthfiana; Putri Sumarsono, Adelia; Rahma Fadilah, Sabrina; Rining Nawangsari, Ertien (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2024)
Policy analysis is a process that can produce instructions or recommendations for problems faced by society. High rainfall in the Pakal area of ​​West Surabaya City can result in flood disasters. The reason the researcher chose the title related to the analysis of government policy in dealing with flood disasters in the Pakal area of ​​West Surabaya was because the researcher was interested in the problems that occurred regarding the community in the city of Surabaya. Apart from that, we want to know whether government policies in Surabaya are running according to the Constitution or vice versa. According to William N Dunn (2000), the theory used is policy analysis. The research method is qualitative. The research results show that the Surabaya City government handled the flood disaster optimally and in accordance with applicable laws